Intervensi Sosial Remaja dalam Meregulasi Emosi dari Berperilaku Agresi Melalui Modifikasi Perilaku dengan Teknik Perilaku Kognitif (CBT) - Adrika Febriany Putri; Irhamni Rahman (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to modify aggression behavior through CBT techniques or cognitive behavioral therapy over a 20-day period. The research method used is using a qualitative approach method. This research also uses an action research approach in providing results to change behavior for the better. In addition, the research also uses descriptive qualitative research in analyzing the data collected during the research process. CBT techniques or cognitive behavioral therapy based on Beck Theory, the three informants learned to recognize negative feelings and thoughts experienced, through situations or events that triggered negative feelings and thoughts in the informants. It can be interpreted that informants will learn to improve skills in how to think, emotion, and act. Therefore, it can be seen that the result of this study is that the CBT Technique with Beck's Theory is sufficient to provide good results in dealing with the three informants who are still relatively young. This CBT technique corrects deviant thoughts in terms of emotions and behavior towards a better direction. Research informants can reduce aggression by 80% from 10-20 times a day to 1-5 times a day.